THE STATUS OF FOREIGN ARBITRATORS UNDER INDONESIAN LAWS - Adolf, Huala (Faculty of Law Universitas Padjadjaran, 2023)
Foreign arbitrators in Indonesia have never been questioned before with regard to their status or legality. The main aim of this article was to analyze the status of foreign arbitrators in the light of the recent Supreme Court of Indonesia’s decision on the PT. Timas Suplindo case (2017). The method used in this article was descriptive-normative of the subject analyzed supported by the case-law, in particular the decision of the Supreme Court of the Republic of Indonesia concerning the issue of foreign arbitrator. This article concluded, while there is an absence of regulation concerning the status of foreign arbitrator in Indonesia, the parties should include and state the legality of the foreign arbitrator in their arbitration clause. This article also recommended, the Arbitration Law should be supplemented with the provision on the status of foreign arbitrator in the future amendment of the Law.